(untitled) (Global Journal of Human-Social Science, 2012)
As Little described learners autonomy has been a new term in the field of applied linguistics It has become one of the objectives of education now This paper reviews definition and some misunderstanding of learners autonomy and discuss the roles of teachers in autonomy